2012
DOI: 10.1007/s11130-012-0319-8
|View full text |Cite
|
Sign up to set email alerts
|

Juice, Pulp and Seeds Fractionated from Dry Climate Primocane Raspberry Cultivars (Rubus idaeus) Have Significantly Different Antioxidant Capacity, Anthocyanin Content and Color

Abstract: Raspberries contain flavonoid antioxidants whose relative concentrations may vary between the juice, pulp, and seed fractions. Oxygen radical absorbance capacity (ORAC), total anthocyanin content, and berry color were determined for six cultivars of primocane raspberries grown in a dry climate (Utah, USA). Significant ORAC differences were found between juice (18.4 ± 0.39 μmol TE/g), pulp (24.45 ± 0.43), and seeds (273.27 ± 11.15) with all Utah cultivars combined. A significantly higher concentration of anthoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Studies by Wallace (2011) and Basu et al (2010) show the benefits of anthocyanins against cardiovascular diseases, cancer among others. Studies by Borges, Degeneve, Mullen, and Crozier (2010) and Snyder, Low, Stocks, Eggett, and Parker (2010) demonstrated that polyphenols, especially anthocyanins, have antimicrobial capacity. However, all these studies have been carried out on fresh fruits and juices, not on the microencapsulated powder of these compounds.…”
mentioning
confidence: 99%
“…Studies by Wallace (2011) and Basu et al (2010) show the benefits of anthocyanins against cardiovascular diseases, cancer among others. Studies by Borges, Degeneve, Mullen, and Crozier (2010) and Snyder, Low, Stocks, Eggett, and Parker (2010) demonstrated that polyphenols, especially anthocyanins, have antimicrobial capacity. However, all these studies have been carried out on fresh fruits and juices, not on the microencapsulated powder of these compounds.…”
mentioning
confidence: 99%
“…It is the fixed oil yielded from the seeds of the Raspberry and its components are fatty acids, and high concentrations of vitamins A and E, so appreciated in the cosmetics and pharmaceutical industries. Its potentials that are high antioxidant capacity and exhibited anti-inflammatory, anti-aging, anti-mutagenic, and antimicrobial properties and also used as an efficient moisturizer and emollient which aids to alleviate oxidative stress in the skin, is utilized in cosmetic emulsions for UV protection [12,13]. It assists to protect cells from oxidative damage and also aids with maintaining the structure of the collagen [13].…”
Section: Rose Water (Rosa Damascena)mentioning
confidence: 99%
“…RSO well-known for its components: fatty acids, vitamin E so appreciated in cosmetics and pharmaceuticals industries. RSO is also known for its high antioxidant capacity and exhibits anti-inflammatory, anti-mutagenic and antimicrobial properties [ 27 ]. RSO is also used in cosmetics as an efficient moisturizer and emollient which helps to reduce the oxidative stress in skin, is used in cosmetic emulsions for UV protection [ 6 ].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%